PENGARUH PROFITABILITAS, STRUKTUR ASET, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Nita Puspita Sari; Samin Samin (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
This study aims to determine the effect of Profitability, Asset Structure, Liquidity, and Capital Structure for the manufacturing company in Indonesia Stock Exchange 2010 - 2013. The study uses secondary data sources of the data derived by the Indonesia Stock Exchange with four years study period, namely 2010-2013. The population in this study a number of 40 companies manufacturing miscellaneous industry sectors listed on the Indonesia Stock Exchange period 2010-2013. Sampling was purposive sampling method with the provisions of these companies include financial statements for duration of the study period and has positive net income and then a total sample of 18 companies. Data analysis using classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination, and profitability, asset structure, and liquidity as independent variabel. The data of this study are qualified classical assumption test and conformance tes models with adjusted R2 of 46,4%. Results of the analysis done of profitability, and liquidity strukturaset significant effect on the capital structure.